Development of a Multimedia-Based Islamic Religious Education Learning Module at the Faculty of Fisheries, Andi Djemma University, Palopo - Muh. Nabil Aditya Nasir; Muhaemin; Edhy Rustan (CV. Edujavare Publishing, 2026)
This study aims to develop a multimedia-based Islamic Religious Education learning module for students at the Faculty of Fisheries, Andi Djemma University, Palopo, in order to improve learning effectiveness, student engagement, and the integration of Islamic values with disciplinary knowledge. The study employed a Research and Development (R&D) approach, involving stages of needs analysis, module design, development, expert validation, revision, implementation, and evaluation. Data were collected through interviews, questionnaires, observations, and learning outcome assessments involving lecturers, media experts, content experts, and students. The findings reveal that the developed multimedia-based module meets high standards of content accuracy, instructional design, media quality, and usability based on expert validation. Students responded positively to the module, demonstrating increased motivation, active participation, conceptual understanding, and satisfaction during the learning process. The integration of interactive multimedia elements, including videos, animations, images, quizzes, and case-based learning activities, enhanced students’ comprehension of Islamic Religious Education while fostering critical thinking and the practical application of Islamic values in academic and professional contexts. Furthermore, the module proved to be an effective learning resource that supports independent learning and technology-enhanced instruction in higher education. Therefore, the study concludes that multimedia-based Islamic Religious Education modules can significantly improve the quality of teaching and learning and are recommended for broader implementation across higher education institutions